CHARACTERIZATION OF NAKAYAMA $m$-CLUSTER TILTED ALGEBRAS OF TYPE $A_n$ - Faisal, Faisal; Muchtadi-Alamsyah, Intan (Journal of the Indonesian Mathematical Society, 2016)
Abstract. For any natural natural number m, the m-cluster tilted algebras are generalization of cluster tilted algebras. These algebras are defined as the endomorphism ofÂ certain objects in m-cluster category called m-cluster tilting objects. Finding such objectin the m-cluster category has become a combinatorial problem. In this article we charac-terize Nakayama m-cluster tilted algebras of type An by geometric description given byBaur and Marsh.DOI :Â http://dx.doi.org/10.22342/jims.22.2.213.93-130